Effects of Several Common Antifungal Drugs (Clotrimazole, Miconazole, Fluconazole) alone and in Combination with Amphotericin B on Candida Species Isolated from Chronic Candidal Vulvovaginitis - Efate alsadat shojaei; Mehraban Falahati; Faride zaini; Parivash kord bache; Parvaneh rahimi moghadam; Mohammad reza aghamirian; Shima Nozari; Ayesheh Makhdoomi; Sekhavatv ameri; Sanam afshar moghadam (Fasa University of Medical Sciences, 2014)
Background; Objective: Candidal vulvovaginitis occurs in female genital by the over growth of candida especially candida albicans. This infection may be resistant to therapy and occasionally becomes chronic. In some patients, this form of infection is recurrent. Moreover, discovering new antifungal drugs and the use of these drugs in new methods encourage mycologists to use these techniques. Therefore, according to the above methods, this research investigated effects of several common antifungal drugs with the use of combination methods against candida species isolated from chronic candidal vulvovaginitis.Materials; Methods: This study carried out on 19 strains of candida albicans that were isolated from recurrent vulvovaginitis. The effects of clotrimazole, miconazole, fluconazole were assessed separately and in combination with amphotericin B on candida albicans using micro dilution methods.Results: The mean Minimum Inhibitory Concentration (MIC) of clotrimazole, miconazole, fluconazole, and amphotericin B were 7.05, 10.7,47, and 0.6 µgr/ml, respectively after 48 hours incubating. Then, the azole antifungal drugs were evaluated in combination with amphotericin B. The two combinations of fluconazole + amphotericin and miconazole + amphotericin with the Fungicidal Inhibitory Concentrations (FIC) of 0.6 and 1, respectively, attracted the most attentions. In addition, comparing the antifungal effects, the most effective drug was amphotericin B with the Minimum Fungicidal Concentration (MFC) of 1.18.Conclusion: In this study, amphotericin B with the least MIC had the best antifungal effect. The most and the least synergic effects of combination therapy were for fluconazole + amphotericin B and Miconazole + amphotericin B, respectively.